Effects of anther‐stigma position on cross‐pollination efficiency in a hermaphroditic plant - Baranzelli, Matias C.; Ochoa‐Sánchez, Manuel; Ramos, Sergio E.; Baena‐Díaz, Fernanda; Sosenski, Paula; Boege, Karina; Domínguez, Cesar A.; Fornoni, Juan (Botanical Society of America, 2024)
Fil: Baranzelli, Matias C. Universidad Nacional Autónoma de México. Instituto de Ecología, Ciudad de México; México.